2013
DOI: 10.1111/bjep.12013
|View full text |Cite
|
Sign up to set email alerts
|

Creativity, visualization abilities, and visual cognitive style

Abstract: The results show that object visualization relates to artistic creativity and spatial visualization relates to scientific creativity, while both are distinct from verbal creativity. Furthermore, our findings demonstrate that style predicts corresponding dimension of creativity even after removing shared variance between style and visualization ability. The results suggest that styles might be a more ecologically valid construct in predicting real-life creative behaviour, such as performance in different profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 54 publications
6
108
1
1
Order By: Relevance
“…Differences between various domains of creativity have already been widely discussed in the literature (Kozhevnikov, Kozhevnikov, Chen & Blazhenkova, 2013;Sawyer, 2006;Simonton, 2008). Additionally, a certain discrepancy in the performance of bilinguals on different types of creativity tasks (e.g., language and figurative creativity) has been found in some studies in the field (Kharkhurin, 2010b(Kharkhurin, , 2012M.…”
Section: Discussionmentioning
confidence: 96%
“…Differences between various domains of creativity have already been widely discussed in the literature (Kozhevnikov, Kozhevnikov, Chen & Blazhenkova, 2013;Sawyer, 2006;Simonton, 2008). Additionally, a certain discrepancy in the performance of bilinguals on different types of creativity tasks (e.g., language and figurative creativity) has been found in some studies in the field (Kharkhurin, 2010b(Kharkhurin, , 2012M.…”
Section: Discussionmentioning
confidence: 96%
“…One possible explanation is that although visualization style and corresponding ability depend on common processing resources (Kozhevnikov, Blazhenkova, & Becker, 2010); style and ability still represent partially independent cognitive constructs. Evidence in favor of this distinction is provided by Kozhevnikov, Chen, and Blazhenkova (2013). They showed that although object and spatial visualization styles and abilities both related to artistic and scientific creativities respectively, visualization style could still reliably predict creativity even after removing the shared variance between style and ability.…”
Section: Individual Differences In Number-space Association 200mentioning
confidence: 99%
“…Based on previous studies relating the linkage between cognitive style and design capabilities [16,19,20] it was assumed, here, that there will be differences in the number of the drawn items in HFD on basis of verbal-visual tendency, and that cognitive style is an intervening variable in HFD test results. Hypothesis was that individuals with visual cognitive style will be presenting more information in HFD test, including organs and accessories and thus will be ranked higher than verbal cognitive style individuals.…”
Section: Discussionmentioning
confidence: 99%